The rise and fall of tobacco smoking and associated rise and fall of coronary atherosclerosis the lethal role of tobacco - Lawson, James S. (Frontiers in Cardiovascular Medicine, 2023)
In this review two new hypotheses are explored, one, that the decline in coronary heart disease is mainly due to a dramatic decline in the prevalence of underlying atherosclerosis and two, that tobacco smoking has been a much greater influence on atherosclerosis than previously estimated. The major outcome of coronary atherosclerosis is myocardial infarction. Between 1900 and 1960 the prevalence of coronary atherosclerosis dramatically rose in young male soldiers. Between 1960 and 2010 the prevalence of coronary atherosclerosis in young US soldiers equally dramatically fell. Understanding the reasons for this rise and fall offers important insights into the causes of atherosclerosis. In 1960 over 50% of US military personnel were tobacco smokers but by 1988 the rate had reduced to 30%. The increased prevalence of coronary atherosclerosis in young soldiers between 1900 and 1960 was mainly due to increased tobacco smoking. An additional influence was an increase in food and sugar consumption. The fall in atherosclerosis between 1960 and 2010 was probably due to a reduction in tobacco smoking and to a lesser extent, control of hypertension and lowering of high serum total cholesterol. In Western populations up to two thirds of the fall in deaths due to myocardial infarction has been shown to be due to declines in the incidence of heart attacks. Based on the data included in this review it is arguable that the main reason for the fall in the incidence of heart attacks is the fall in the prevalence of underlying coronary atherosclerosis. The adverse influences of tobacco have been well documented. However the enormity of these adverse influences has not been recognised. Over 50% of men continue to smoke tobacco in China, Indonesia, Russia and middle eastern countries. Based on the experience of Western countries over half of these men will die of smoking related conditions.